Nanoscale pore structure characterization of the Bakken shale in the USA - Liu, K.; Ostadhassan, M.; Zhou, J.; Gentzis, T.; Rezaee, Reza (Elsevier Ltd, 2017)
Understanding the pore structures of unconventional reservoirs such as shale can assist in estimating their elastic transport and storage properties, thus enhancing the hydrocarbon recovery from such massive resources. Bakken Shale Formation is one of the largest shale oil reserves worldwide located in the Williston Basin, North America. In this paper, we collected a few samples from the Bakken and characterized their properties by using complementary methods including X-ray diffraction (XRD), N 2 and CO 2 adsorption, and Rock-Eval pyrolysis. The results showed that all range of pore sizes: micro ( < 2 nm), meso (2–50 nm) and macro-pores ( > 50 nm) exist in the Bakken shale samples. Meso-pores and macro-pores are the main contributors to the porosity for these samples. Compared with the Middle Bakken, samples from Upper and Lower Bakken own more micro pore volumes. Fractal dimension analysis was performed on the pore size distribution data, and the results indicated more complex po re structures for samples taken from the Upper and Lower Bakken shales than the Middle Bakken. Furthermore, the deconvolution of the pore distribution function from the combination of N 2 and CO 2 adsorption results proved that five typical pore size families exist in the Bakken shale samples: one micro-pore, one macro-pore and three meso-pore size families. The studies on the correlations between the compositions and the pore structures showed that mostly feldspar and pyrite affect the total pore volume of samples from Middle Bakken Formation whereas clay dominates the total pore volume of samples from Upper/Lower Bakken Formation. TOC and clay content are the major contributors to the micro-pore size family in the Upper/Lower Bakken. Also, it was observed that the increase of hard minerals could increase the percentage of macro-pore family in the Middle Bakken Formation.